2005
DOI: 10.1128/jvi.79.20.13105-13115.2005
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of Respiratory Syncytial Virus Replication Target Cotranscriptional mRNA Guanylylation by Viral RNA-Dependent RNA Polymerase

Abstract: Respiratory syncytial virus (RSV) is a major cause of respiratory illness in infants, immunocompromised patients, and the elderly. New antiviral agents would be important tools in the treatment of acute RSV disease. RSV encodes its own RNA-dependent RNA polymerase that is responsible for the synthesis of both genomic RNA and subgenomic mRNAs. The viral polymerase also cotranscriptionally caps and polyadenylates the RSV mRNAs at their 5 and 3 ends, respectively. We have previously reported the discovery of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
108
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(116 citation statements)
references
References 42 publications
(51 reference statements)
4
108
1
3
Order By: Relevance
“…The D714A mutant efficiently produced the cap structures (lane 11), demonstrating that the RdRp active site is not required for the capping reaction. The R1221A and R1221H mutants were inactive (lanes 16 and 18), whereas the R1221K mutant showed 2% of the WT activity (lane 17) and the other mutants retained capping activities (lanes 14,15,[19][20][21][22]. We also measured the capping activity of the mutants with ½α-32 P GTP, instead of ½α-32 P GDP, as the substrate and confirmed that the H1227, R1228, and R1221 residues are required for the capping activity (Fig.…”
Section: The Hr Motif In the L Protein Is Required For The Prntase Acmentioning
confidence: 91%
See 1 more Smart Citation
“…The D714A mutant efficiently produced the cap structures (lane 11), demonstrating that the RdRp active site is not required for the capping reaction. The R1221A and R1221H mutants were inactive (lanes 16 and 18), whereas the R1221K mutant showed 2% of the WT activity (lane 17) and the other mutants retained capping activities (lanes 14,15,[19][20][21][22]. We also measured the capping activity of the mutants with ½α-32 P GTP, instead of ½α-32 P GDP, as the substrate and confirmed that the H1227, R1228, and R1221 residues are required for the capping activity (Fig.…”
Section: The Hr Motif In the L Protein Is Required For The Prntase Acmentioning
confidence: 91%
“…The precise roles of the G1154 and T1157 residues in the capping reaction, if any, remain unknown. Interestingly, Liuzzi et al (21) have recently found that small molecule inhibitors against cotranscriptional mRNA capping by the L protein of human respiratory syncytial virus (Paramyxoviridae) prevent virus replication in vivo, and mutant viruses resistant to the inhibitors carry mutant L proteins with amino acid substitutions in the vicinity of the HR motif within the block V. Thus, the block V of the NNS RNA viral L protein appears to be involved in mRNA capping, although the exact boundary of the putative PRNTase domain remains unknown.…”
Section: The Hr Motif In the L Protein Is Required For The Prntase Acmentioning
confidence: 99%
“…The role of the compounds, if any, during L-P, N-P, or L-N-P interaction in the cells can be tested by standard immunoprecipitation using plasmid-expressed proteins. Recently, Luizzi et al (Liuzzi et al, 2005), have shown that similar small molecules, that are structurally different from C5 and C7 inhibited RSV replication. The compounds, identified by HTS assay (Mason et al, 2004), appear to block synthesis of RSV mRNA apparently by inhibiting guanylylaion of viral transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of a second inhibitor of RSV polymerase through screening of a chemical library with a poly(A) capture assay was reported in 2004 by researchers from Boehringer Ingelheim (Mason et al, 2004). Shortly after, a series of imidazo [4,5-h]isoquinoline-7,9-dione inhibitors were synthesized that target the 5' capping of viral mRNA transcripts (Liuzzi et al, 2005). The most potent compound, compound D, exhibited an antiviral EC 50 = 0.021 µM (polymerase IC 50 = 0.089 µM) with a SI ≤ 400.…”
Section: Rna-dependant Rna Polymerase Inhibitorsmentioning
confidence: 99%